Levonorgestrel Concentration in a Single Rod Implant Users for Six Months - Eka R. Gunardi (Indonesian Journal of Obstetrics and Gynecology, 2011)
Objective: This research was conducted to measure levonorgestrel serum concentration Monoplant® after six months of usage. Method: Thirty healthy women, 20 - 40 years old, and after been proven for fertility, had implants on their body. Levonorgestrel serum levels were measured monthly from the first month to the sixth month. Result: Levonorgestrel serum concentration was still above 200 pg/ml until the sixth month. First month and second month serum concentration was not recorded while data for the following months were 338.9 pg/ml, 424.8 pg/ml, 320.3 pg/ml, and 337.5 pg/ml. Conclusion: Levonorgestrel serum concentration in Monoplant® users was still above contraceptive level until six months. [Indones J Obstet Gynecol 2011; 35-3: 122-7] Keywords: single rod implant Monoplant®, levonorgestrel serum concentration